Learning to listen to trans and gender diverse children: A Response to Zucker (2018) and Steensma and Cohen-Kettenis (2018). Issue 2 (3rd April 2018) - Winters, Kelley; Temple Newhook, Julia; Pyne, Jake; Feder, Stephen; Jamieson, Ally; Holmes, Cindy; Sinnott, Mari-Lynne; Pickett, Sarah; Tosh, Jemma
ABSTRACT: The authors answer recent responses by Steensma & Cohen-Kettenis (2018 ) and Zucker (2018 ) to our critical commentary on "desistance" stereotypes and their underlying research on trans and gender diverse children (Temple Newhook et al., 2018 ). We provide clarification in the following areas: (1) the scope of our paper; (2) our support of longitudinal studies; (3) consequences of harm to trans and gender diverse children; (4) clinical practice implications; (5) concerns about validity of research methodology; and (6) the importance of learning to listen to trans and gender diverse children.